Phase IIa Global Study Evaluating Rituximab for the Treatment of Pediatric Patients With Granulomatosis With Polyangiitis or Microscopic Polyangiitis. Issue 1 (5th December 2021) - Brogan, Paul; Yeung, Rae S. M.; Cleary, Gavin; Rangaraj, Satyapal; Kasapcopur, Ozgur; Hersh, Aimee O.; Li, Suzanne; Paripovic, Dusan; Schikler, Kenneth; Zeft, Andrew; Bracaglia, Claudia; Eleftheriou, Despina; et al.
Abstract : Objective: To assess the safety, tolerability, pharmacokinetics, and efficacy of rituximab (RTX) in pediatric patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA). Methods: The Pediatric Polyangiitis Rituximab Study was a phase IIa, international, open‐label, single‐arm study. During the initial 6‐month remission‐induction phase, patients received intravenous infusions of RTX (375 mg/m 2 body surface area) and glucocorticoids once per week for 4 weeks. During the follow‐up period, patients could receive further treatment, including RTX, for GPA or MPA. The safety, pharmacokinetics, pharmacodynamics, and exploratory efficacy outcomes with RTX were evaluated. Results: Twenty‐five pediatric patients with new‐onset or relapsing disease were enrolled at 11 centers (19 with GPA [76%] and 6 with MPA [24%]). The median age was 14 years (range 6–17 years). All patients completed the remission‐induction phase. During the overall study period (≤4.5 years), patients received between 4 and 28 infusions of RTX. All patients experienced ≥1 adverse event (AE), mostly grade 1 or grade 2 primarily infusion‐related reactions. Seven patients experienced 10 serious AEs, and 17 patients experienced 31 infection‐related AEs. No deaths were reported. RTX clearance correlated with body surface area. The body surface area–adjusted RTX dosing regimen resulted in similar exposure in both pediatric and adult patients with GPA or MPA. Remission, according to the Pediatric Vasculitis Activity Score, was achieved in 56%, 92%, and 100% of patients by months 6, 12, and 18, respectively. Conclusion: In pediatric patients with GPA or MPA, RTX is well tolerated and effective, with an overall safety profile comparable to that observed in adult patients with GPA or MPA who receive treatment with RTX. RTX is associated with a positive risk/benefit profile in pediatric patients with active GPA or MPA.